Pengembangan Website Profil dan Layanan Percetakan dengan Model Prototyping untuk Meningkatkan Pemasaran pada CV. Percetakan Sapitri - Dandi Saputra; Ferza Ramadhon; Welman Saputra; Maulana Ardhiansyah; Fajar Agung Nugroho (OKTAL : Jurnal Ilmu Komputer dan Sains, 2026)
The development of information technology plays an important role in supporting marketing strategies and improving services in the printing service industry. CV. Percetakan Sapitri still relies on conventional marketing and ordering methods, which limits market reach and service efficiency. This study aims to develop a company profile and printing service website using the prototyping model as a digital solution to enhance marketing effectiveness. The prototyping model was chosen because it allows direct user involvement throughout the system development process through iterative evaluation and refinement. The developed website provides features such as company profile, list of services and prices, printing gallery, and an online ordering form. System testing was conducted using the Black Box Testing method to ensure that all functions operate as expected. The results indicate that the website facilitates easier access to service information, accelerates the ordering process, and supports the expansion of marketing reach. Therefore, the prototyping-based website development contributes positively to digital transformation and competitiveness improvement at CV. Percetakan Sapitri.